ON REPLACEMENT PIPE TUBING IN GAS WELLS FIELDS IN THE LATEST, THE FINAL STAGE OF PRODUCTION IN ABNORMALLY LOW FIELD PRESSURES - Sergey Anatol’evich Parosochenko; Yulianna Olegovna Sizova; Konstantin Nikolaevich Denyak (Вестник Северо-Кавказского федерального университета)
The possibility of using reinforced polyethylene pipes for the replacement of tubing to a smaller diameter due to technological necessity in gas wells in the final stages of operation is offered in this article. We proposed the new design of the end connections for reinforced polyethylene pipes. For test of the end connections have been constructed a test rig, and have been tested end connections with a segment of the pipe. It is proposed a kit of parts needed for to use reinforced polyethylene pipes as tubing string.